International Information - Карпчук, Наталія Петрівна; Karpchuk, Nataliia P. (Lesya Ukrainka Eastern European National University, 2018)
Sociology as a science and its place in the humanities and social science. The main functions of sociology. Background of sociology. The place and role of social research in the knowledge of social phenomena. Methods of collecting primary data. The social structure of society. Sociology of work and industrial relations. Sociology of family life and leisure. Sociology of education and culture. Sociology of personality.
Keywords: міжнародна інформація; інформаційно-комунікаційна політика; міжнародна інформаційна безпека; зовнішньополітичні комунікативні технології; інформаційна етика; international information; information and communication policy; international information security; foreign policy communication instruments; information ethics